Boosting Competitiveness to Grow Out of Debt : Can Ireland Find a Way Back to Its Future? - Nkusu, Mwanza (IMF Working Papers; Working Paper ;, 2013)
This paper investigates the prospects for Ireland to grow its economy against the backdrop of high indebtedness. The paper uses vector autoregressive analysis to explore the interlinkages among competitiveness, exports, economic growth, and fiscal performance. The emerging conclusion is that Ireland, which has regained cost competitiveness following the crisis-driven fall in domestic prices, is poised to return to its path of strong exports and economic growth and lower imbalances provided that it maintains competitiveness, though a pickup in external demand is critical. Three main findings underpin this conclusion. First, external demand is an important driver of exports and also the single most important determinant of Ireland's GDP and government revenue. Second, declines in price competitiveness, featured by real effective exchange rate (REER) appreciations, restrain exports and economic growth. Third, exports boost output, which in turn enhances fiscal performance.